The right of a platform worker to decide whether and when to work: An obstacle to their employee status? - Rosin Annika (Intersentia, 2025)
The employment status of platform workers has been vividly discussed in recent years. Digital platforms often argue that the workers’ freedom to decide whether and when to work speaks to their self-employment. The scarce case law of the Court of Justice of the European Union (CJEU) as well as the new proposal for a Directive on platform work appears to indicate that opinion is shared. However, the Member States can guarantee better protection to platform workers. The working arrangements of platform workers are similar to zero-hours work in which the worker also has the right to refuse offered tasks. In some countries, such as Finland, zerohours workers are explicitly considered as employees. Nevertheless, the general definition of the employment contract requires the commitment on behalf of the employee to perform work. This contradiction makes the employment status of zero-hours workers as well as platform workers unclear.
In this article I analyse whether and how the right to decide whether and when to work affects the employment status of food delivery couriers working through digital platforms. I use Wolt and Foodora as examples. The issue is analysed in the light of Finnish regulation and European Union law.
I argue that even though the case law of the CJEU and the proposal for a Directive on platform work regard the right of a food delivery courier to decide whether and when to work as evidence against their employee status, the couriers can obtain this status through the regulation of zerohours contracts. Regardless of the fact that generally the conclusion of an employment contract requires the commitment on behalf of the worker to perform work, zero-hours workers are
explicitly and exceptionally exempted from this requirement. As the couriers can be classified as zero-hours workers, their freedom to choose whether and when to work does not preclude their classification as employees.